A European dilemma: The EU export control regime on dual-use goods and technologies - Hamed Alavi; Tatsiana Khamichonak (DANUBE: Law, Economics and Social Issues Review, 2016)
Export controls for dual-use items are an important constituent element of both the security policies of state exporters and WMD non-proliferation efforts. Dual-use goods and technologies can be used for both civil and military purposes, which requires careful oversight over their export to countries that are considered unfriendly or have ambiguous foreign policy attitudes. By their very nature, dual-use items may be used both to further legitimate ends, like promoting technological development and strengthening economic ties, and to aid in unwarranted acts. State exporters are faced with the responsibility of balancing the security objectives pertaining to exports of dual-use items with the competitiveness of local economies. The paper discusses the EU export control regime and EU membership in international export control groups. In doing so, comparative and normative research methods are chosen to analyze existing literature on Council Regulation 428/2009 and other international export control groups, including the Wassenaar Arrangement, the Missile Technology Control Regime (MTCR), the Australia Group (AG) and the Nuclear Suppliers Group (NSG). The paper will conclude by identifying shortcomings and addressing possible amendments to the regulation.
Keywords: 330; Dual-use Items; Security Policy; Weapons of Mass Destruction; Export Control